Telomere Interacting Proteins and TERRA Regulation - Pérez-Martínez, Lara; Wagner, Tina; Luke, Brian (Frontiers in Genetics, 2022)
Telomere shortening rates inversely correlate with life expectancy and hence it is critical to understand how telomere shortening is regulated. Recently, the telomeric non-coding RNA, TERRA has been implicated in the regulation of replicative senescence. To better understand how TERRA is regulated we employed a proteomics approach to look for potential RNA regulators that associate with telomeric sequences. Based on the results, we have identified proteins that may regulate TERRA in both a positive and negative manner, depending on the state of the telomere. In this mini-review, we discuss and speculate about these data to expand our understanding of TERRA and telomere interactors with respect to telomere shortening dynamics.